Design and Efficiency Optimization of Distributed Laser Wireless Power Transmission Systems Through Centralized Scheduling and Current Regulation - Liangrong Sun; Jinsong Kang; Yunfeng Bai; Pengjia Jin (Photonics)
This paper presents an efficiency optimization method for laser wireless power transmission (LWPT) system, focusing on the coordination and control of multiple laser diodes. A distributed laser wireless power transmission (D-LWPT) system is proposed, which includes multiple independent and parallel power transmission chains. The system has the characteristics of power scalability, redundancy, and control flexibility. The efficiency characteristics of each key component in the LWPT system are discussed. Due to the internal losses of the laser, the transmission efficiency is also affected by the transmission power. For distributed architecture, its flexibility allows for the rational allocation of transmission power. To achieve optimal efficiency, a central scheduling controller is designed to regulate the current of LDs. A swarm intelligence-based optimization algorithm is used to determine the optimal operating current. This significantly improves the system’s efficiency and ensures real-time control. Experimental results validate the effectiveness of the proposed techniques. The DC to DC efficiency of the power transmission chain can reach over 14%, and the photovoltaic array can output a maximum power of over 130 W. The impact of beam combination on the efficiency and output power of PV arrays is less than 3%, indicating that the distributed structure does not affect system performance. The experimental results show that the proposed efficiency optimization method has excellent power following performance (algorithm execution time < 10 ms) and effective efficiency optimization performance. Under light load conditions, the LDs’ efficiency is optimized from 27.5% to 45.0%, and under medium load conditions, it is optimized from 41.5% to 44.5%. This distributed structure and efficiency optimization method provide a solution for improving the performance of LWPT systems.